A multiregional proteomic survey of the postnatal human brain. (December 2017) - Carlyle, Becky; Kitchen, Robert; Kanyo, Jean; Voss, Edward; Pletikos, Mihovil; Sousa, André; Lam, TuKiet; Gerstein, Mark; Sestan, Nenad; Nairn, Angus
Abstract Detailed observations of transcriptional, translational and post-translational events in the human brain are essential to improving our understanding of its development, function and vulnerability to disease. Here, we exploited label-free quantitative tandem mass-spectrometry to create an in-depth proteomic survey of regions of the postnatal human brain, ranging in age from early infancy to adulthood. Integration of protein data with existing matched whole-transcriptome sequencing (RNA-seq) from the BrainSpan project revealed varied patterns of protein–RNA relationships, with generally increased magnitudes of protein abundance differences between brain regions compared to RNA. Many of the differences amplified in protein data were reflective of cytoarchitectural and functional variation between brain regions. Comparing structurally similar cortical regions revealed significant differences in the abundances of receptor-associated and resident plasma membrane proteins that were not readily observed in the RNA expression data. Quantitative mass spectrometry was used to produce a proteomic survey of postnatal human brain regions. Compared to matched RNA-seq, protein levels showed more regional variation, especially for membrane-associated proteins in the neocortex.